Sequence Analysis of the Matrix (M2) Protein Gene of Avian Pneumovirus Recovered from Turkey Flocks in the United States - Dar, Arshud M. (American Society for Microbiology, 2003)
We here report the comparative sequence and phylogenetic analysis of the avian pneumovirus subgroup C (APV C) matrix (M2) gene of cell culture-adapted isolates and clinical samples. Limited heterogeneity was observed among the M2 sequences, suggesting that diagnostic tests and vaccines against APV C are likely to exhibit broad cross-reactivity.